Multidisciplinary Management of Hepatolithiasis at a Tertiary Care Center in Nepal - Maharjan, Narendra; Joshi Lakhey, Paleswan; Ghimire, Bikal; Kansakar, Prasan BS; Bhandari, Ramesh S (Journal of Institute of Medicine Nepal, 2020)
Introduction Hepatolithiasis is more prevalent in Far-East than in Middle-East countries. There are various treatment modalities available for hepatolithiasis like surgical and non-surgical procedures. Non-surgical procedures have higher recurrence rate. Methods This is a descriptive retrospective study of the clinical data of hepatolithiasis patients treated at Tribhuvan University Teaching Hospital (TUTH), Maharajgunj from April 2016 to October 2019. Results There were 14 patients and mean age was 45.8±14.8 years. It was more common in female (F: M = 4:3). Left sided hepatolithiasis was the most common type (50%). One (7.1%) patient had bilateral hepatolithiasis associated with unresectable cholangiocarcinoma. Eight (57.1%) patients were treated with surgical procedures; four (28.6%) patients underwent interventional radiological procedures and remaining two (14.3%) patients had combined surgical and intervetional radiological procedures. Complete stone clearance was achieved in 11 patients (78.57%). In surgical therapy group, seven out of eight (87.5%) patients achieved the complete stone clearance; two out of four (50%) patients in interventional radiology group and all patients in combined therapy group achieved the clearance. There was no recurrence among those patients who had complete stone clearance and there was no mortality. Conclusion The management of hepatolithiasis should involve multi-modality (surgical and non-surgical) therapeutic techniques available, in order to achieve complete stone clearance and prevent the complications.